A General Model of Drug Prescription - Séné, B.; Venot, A.; de Zegher, I.; Milstein, C.; Errore, S.; de Rosis, F; Strauch, G. (Methods of Information in Medicine, 1995)
Currently, there is no widely accepted structured representation of drug prescription. Nevertheless, a structured representation is required for entering and storing drug prescriptions avoiding free text in computerized systems, and for drug prescription reviews. Derived from part of the work of the European OPADE project, we describe an object-oriented model of drug prescription which incorporates important concepts such as the phase and triggering event concepts. This model can be used to record all drug prescriptions, including infusions, in a structured way avoiding free text. The phase concept allows the storage of sequentially ordered dosage regimens for a drug within the same prescription. The prescription triggering event concept allows recording of the administration of a drug conditional to dates, symptoms and clinical signs, medical procedures, and everyday life events. This model has been implemented within the OPADE project; the corresponding aspects of the user interface are presented to show how this model can be used in practice. Even if other new attributes may be added to the described objects, the structure of this model is suitable for general use in software which requires the entry, storage and processing of drug prescriptions.
Keywords: Drug Prescription; Computerized Drug Prescription System; Object-Oriented Model